2022
DOI: 10.3390/biomedicines10102413
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Regulation in Cancer Stem Cells

Abstract: Cancer stem cells (CSCs) represent a small subset of slowly dividing cells with tumor-initiating ability. They can self-renew and differentiate into all the distinct cell populations within a tumor. CSCs are naturally resistant to chemotherapy or radiotherapy. CSCs, thus, can repopulate a tumor after therapy and are responsible for recurrence of disease. Stemness manifests itself through, among other things, the expression of stem cell markers, the ability to induce sphere formation and tumor growth in vivo, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 174 publications
0
6
0
Order By: Relevance
“…Consequently, the efficacy of radiation treatment is linked to a cell's ability to control ROS levels through various detoxification mechanisms. These include enzymes like manganese or copper-zinc superoxide dismutase, catalases, and glutathione peroxidase (GPX)/reductase that convert oxygen radicals to hydrogen peroxide and subsequently water, and nonenzymatic antioxidants, such as urate, glutathione, polyamines, vitamins E, A, and C. Tight regulation of ROS levels is also important for maintaining stemness; hence all pathways described above influence redox homeostasis 130 . GPX4 is one such regulator that protects cells from lipid oxidation and thereby protects from ferroptotic cell death 131 .…”
Section: Strategies For Enhancing Susceptibility To Conventional Radi...mentioning
confidence: 99%
“…Consequently, the efficacy of radiation treatment is linked to a cell's ability to control ROS levels through various detoxification mechanisms. These include enzymes like manganese or copper-zinc superoxide dismutase, catalases, and glutathione peroxidase (GPX)/reductase that convert oxygen radicals to hydrogen peroxide and subsequently water, and nonenzymatic antioxidants, such as urate, glutathione, polyamines, vitamins E, A, and C. Tight regulation of ROS levels is also important for maintaining stemness; hence all pathways described above influence redox homeostasis 130 . GPX4 is one such regulator that protects cells from lipid oxidation and thereby protects from ferroptotic cell death 131 .…”
Section: Strategies For Enhancing Susceptibility To Conventional Radi...mentioning
confidence: 99%
“…In a previous study, we suggested that CSCs have a strong peroxidative lipid scavenging capacity and that the GPX4-GSH axis, a major mechanism of peroxidative lipid scavenging, is upregulated in CSCs and contributes to the acquisition and maintenance of stemness characteristics ( 15 ). A growing number of studies have shown that the GPX4-GSH axis plays an important antioxidant role in promoting or maintaining the stemness profile and drug resistance of colorectal, gastric, breast, pancreatic, liver, biliary, lung, and glioma CSCs ( 27 , 34 , 128 133 ).…”
Section: Increased Lipid Peroxide Scavenging Capacity In Cscsmentioning
confidence: 99%
“…Secondly, interactions between CSCs and their niche maintain self-renewal and promote drug resistance, metastasis, and relapse. Many studies have shown that CSCs visibly alter iron metabolism ( 9 ), lipid metabolism ( 10 ), multiple cell signaling ( 11 ), tumor microenvironment ( 12 , 13 ), redox regulation ( 14 , 15 ), epithelial-mesenchymal transformation (EMT) ( 7 , 16 ), and other aspects. In addition, due to their plasticity, quiescent CSCs can transform into cycling CSCs, leading to metastasis and relapse ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, the experimental oxygen levels were 7% for physoxia and 4% for hypoxia (mild). Typically, studies of CSC utilize cell culture conditions at room oxygen levels (21%) and control oxidative stress by adding antioxidants to the media 28 . However, no cells in internal organs, with the exception of cells lining the alveoli in the lungs, grow in 21% oxygen, and in the tumor microenvironment the oxygen levels can be very low.…”
Section: Introductionmentioning
confidence: 99%